Beyond cascade screening: detection of familial hypercholesterolaemia at childhood immunization and other strategies. Issue 4 (August 2017) - Martin, Andrew C.; Bell, Damon A.; Brett, Tom; Watts, Gerald F.
Abstract : Purpose of review: Familial hypercholesterolaemia is a common genetic disorder that accelerates premature coronary heart disease. Although effective treatments are available, the majority of individuals remain undiagnosed. We review new evidence for improving the detection of familial hypercholesterolaemia. Recent findings: Recent studies have demonstrated that universal screening of children for familial hypercholesterolaemia may be highly effective at the time of immunization if combined with reverse cascade testing of adult family members, who have a more immediate risk of a coronary event. Alerts on laboratory reports and the application of bioinformatics to electronic health records may also be useful for identifying familial hypercholesterolaemia in community settings. Effective detection, diagnosis, and codification of familial hypercholesterolaemia are essential for the development of registries. Summary: Although the cost-effectiveness of screening programs for familial hypercholesterolaemia in childhood remains to be established, combining universal and reverse cascade screening, complemented by opportunistic identification of individuals in high-risk settings, use of laboratory alerts, and screening of electronic health records are likely to have a high yield in the detection of familial hypercholesterolaemia in the community.